Consequences of Gender Differences in Stressful Behavior as a Function of Psychological Hardiness and Need Structure: Examining Gender Differences in Stress and Resilience (Journal of Advances and Scholarly Researches in Allied Education, 2016)
One of the most prevalent concerns contained in the hardiness literature is the issue of whether the structure is equally essential for both men and women. Using a multi-group confirmatory factor empirical method, this topic was examined from a more basic viewpoint by analyzing the equivalence of metrics through gender in a test of toughness, the 15-item Dispositional Resilience Scale [DRS-15 Bartone, P. T. It was (1995). A minimal range of toughness. Paper delivered at the annual conference of the American Psychological Society, New York.]. While the findings indicated any non-equivalence relative to the control subscale, follow-up analyzes analyzing the gender disparity in the two non-equivalent elements found that the gender influence was negligible. The gender influences reported showed that women were more likely to accept these products than men. In view of the specific parameters used to evaluate equivalence and the limited proof of prejudice observed, it is concluded that the findings generally imply gender equivalence in the DRS-15.